Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð»ÐµÐ¹ÐºÐ¾ÐºÐ¾Ð½Ñ†ÐµÐ½Ñ‚Ñ€Ð°Ñ‚Ð° ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð½Ð° Ñ€ÐµÐ³ÐµÐ½ÐµÑ€Ð°Ñ‚Ð¾Ñ€Ð½ÑƒÑŽ Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚ÑŒ ÐºÐ¾Ð¶Ð¸ Ð² ÐºÑƒÐ»ÑŒÑ‚ÑƒÑ€Ðµ in vitro - Tsutsayeva, A. A.; Volina, V. V.; Sokol, L. V.; Zhulikov, O. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2009)
The effect of human cord blood cryopreserved cell leukoconcentrate, suspended in autologous plasm (LHCB preparation) on in vitro cultured human skin morphology in different terms, has been studied. Skin was cultured on an agarised medium, supplemented with 17% embryonic serum (control) and 10% LHCB preparation (experimental group). The skin viability in vitro was maintained for 5–7 days longer in the presence of LHCB preparation compared to the control group. Under LHCB effect in cultured skin flaps there was an increase in fibroblast and fibrous structure amount, that enables concluding about the stimulation of both processes of fibroblast proliferation and synthesis of fibrous structures in derma.